1999
DOI: 10.1084/jem.189.4.615
|View full text |Cite|
|
Sign up to set email alerts
|

Endotoxin-tolerant Mice Have Mutations in Toll-like Receptor 4 (Tlr4)

Abstract: Bacterial lipopolysaccharide (LPS) provokes a vigorous, generalized proinflammatory state in the infected host. Genetic regulation of this response has been localized to the Lps locus on mouse chromosome 4, through study of the C3H/HeJ and C57BL/10ScCr inbred strains. Both C3H/HeJ and C57BL/10ScCr mice are homozygous for a mutant Lps allele (Lpsd/d) that confers hyporesponsiveness to LPS challenge, and therefore exhibit natural tolerance to its lethal effects. Genetic and physical mapping of 1,345 backcross pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
1,026
5
17

Year Published

2002
2002
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 1,447 publications
(1,074 citation statements)
references
References 44 publications
(55 reference statements)
26
1,026
5
17
Order By: Relevance
“…Comparative studies of innate immune responses to common bacterial antigens are valuable in understanding shared mechanisms of cell recognition within and between taxa, as such endeavours are more complicated with higher vertebrates because of the superimposed action of the adaptive immune system. Exploitation of such comparative studies with LPS has resulted in the discovery of mammalian homologues of Drosophila Toll proteins, important in the cell-signalling responses to microbial molecules [41].…”
Section: Discussionmentioning
confidence: 99%
“…Comparative studies of innate immune responses to common bacterial antigens are valuable in understanding shared mechanisms of cell recognition within and between taxa, as such endeavours are more complicated with higher vertebrates because of the superimposed action of the adaptive immune system. Exploitation of such comparative studies with LPS has resulted in the discovery of mammalian homologues of Drosophila Toll proteins, important in the cell-signalling responses to microbial molecules [41].…”
Section: Discussionmentioning
confidence: 99%
“…Data analysis for the crosses to each of the two C3H mouse strains was kept separate throughout this study for two reasons: first, we have shown a small but significant difference in survival time between the C3Ou and C3 strains, and second, the C3 strain is known to carry a nonfunctional allele of the Tlr4 locus. 21,22 Tlr4-mediated responses have previously been implicated in the onset of tissue pathology and morbidity in the context of C. rodentium infection. 20 Separate analyses would enhance our ability to distinguish common as well as distinct genetic factors controlling survival to C. rodentium infection in the C3Ou and C3 mouse strains.…”
Section: Segregation Of Survival Phenotype In F2 Crossesmentioning
confidence: 99%
“…80,81 Highresolution genetic, physical and transcriptional maps of the area were thereafter generated 82,83 and led to the identification of Tlr4 as a candidate for Lps. 83,84 Three different Tlr4 mutant alleles were identified: C3H/HeJ mice present a single missense mutation resulting in a proline for histidine substitution at codon 712 within the signaling domain; 84,85 in C57BL/10ScCr mice, there were no Tlr4 transcripts detected 84,85 as a consequence of a 75 kb chromosomal deletion encompassing the whole Tlr4 gene; 86 the mutation identified in C57BL/6.KB2-mnd Tlr4 consists in a complete deletion of exon II. This mutation leads to a frameshift resulting in the appearance of a stop codon just downstream of the exon junction.…”
Section: Tlr4mentioning
confidence: 99%